Peacekeeping in Africa by the United Nations and the African Union - (:unkn) unknown (My University, 2014)
Maintaining international peace and security is the primary purpose of the Charterof the United Nations after the Second World War. By Article 2 § 4, the Charter states "theprinciple of non-threat and non-use of force" and thus aims to put a definitive end to armedconflicts. However, the African continent seems not to max out and illustrates not only by avery large number of armed conflicts but also by the ongoing efforts of the United Nations tokeep the peace. These efforts are supported regionally by the African Union, a regionalorganization established by African States in 2002 to replace the Organization of AfricanUnity. The persistence of armed conflicts on the continent, however, leads to question theeffectiveness of peacekeeping in Africa by the United Nations and the African Union, as wellas the mechanisms established by both organizations to achieve with such effectiveness.Consideration of this issue is discussed considering the two major characteristics ofpeacekeeping, namely the institutional aspect and the material aspect of peacekeeping,considered one and the other in terms of their effectiveness.For the institutional aspect, the study focuses on the organs actually created by the UN andthe African Union for peacekeeping in Africa, the cooperation between these organs, as wellas the support provided by the UN for the capacity-building of the African Union.For the material aspect, it is the specific terms of implementations of peacekeeping that areraised here. This requires a review of the effectiveness of the peacekeeping operations.
Keywords: African Research